The structural changes of upper airway and newly developed sleep breathing disorders after surgical treatment in class III malocclusion subjects. Issue 22 (June 2017) - Lee, Ui Lyong; Oh, Hoon; Min, Sang Ki; Shin, Ji Ho; Kang, Yong Seok; Lee, Won Wook; Han, Young Eun; Choi, Young Jun; Kim, Hyun Jik
Abstract : Abstract: Bimaxillary surgery is the traditional treatment of choice for correcting class III malocclusion which is reported to cause an alteration of oropharyngeal structures and upper airway narrowing that might be a predisposing factor for obstructive sleep apnea (OSA). This study aimed to analyze sleep parameters in class III malocclusion subjects and ascertain the prevalence of snoring or OSA following bimaxillary surgery. A total of 22 patients with Le Fort I osteotomy and mandibular setback for class III malocclusion were prospectively enrolled. All patients received endoscopic examination, cephalometry, 3-dimensional computed tomography (3D-CT), and sleep study twice at 1 month before and 3 months after surgery. The patient population consisted of 5 males and 17 females with a mean body mass index of 22.5 kg/m 2 and mean age of 22.1 years. No patients complained of sleep-related symptoms, and the results of sleep study showed normal values before surgery. Three patients (13%) were newly diagnosed with mild or moderate OSA and 6 patients (27%) showed increased loudness of snoring (over 40 dB) after bimaxillary surgery. According to cephalometric analysis and 3D-CT results, the retropalatal and retroglossal areas were significantly narrowed in class III malocclusion patients, showing snoring and sleep apnea after surgery. In addition, the total volume of the upper airway was considerably reduced following surgery in the same patients. Postoperative narrowing of the upper airway and a reduction of total upper airway volume can be induced, and causes snoring and OSA in class III malocclusion subjects following bimaxillary surgery.